Is there lemma-based language control? The influence of language practice and language-specific item practice on asymmetrical switch costs. Issue 4 (21st April 2017) - Declerck, Mathieu; Philipp, Andrea M.
ABSTRACT: Several models have proposed that language control occurs between language representations, such as language tags, and between lemmas. Yet, most research has solely focused on language-control processes between language representations. In the present study, we investigated whether language control can also occur between lemmas by allowing bilinguals to practice a language or language-specific items prior to a language-switching task, and thus change the relative activation of the language representations and/or lemmas. By changing the activation levels, relatively more language control should occur for this language representation and/or lemma relative to their translation-equivalent due to the reactive nature of language control. The results showed that this was all the more so when language-specific items were practiced than when merely a language was practiced. Hence, the current study provides evidence that language control is not restricted to language representations, but could also occur between lemmas.